2002
DOI: 10.1046/j.1365-2257.2002.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of bone marrow examination in staging Hodgkin's disease: experience in México

Abstract: We assessed the value of bone marrow biopsy prospectively in a group of 91 individuals with Hodgkin's disease. The median age of our population was 29 years (range 4-87 years); 59 were males. Most patients (45%) had nodular sclerosing disease and most patients (44%) were in pathological stage II at diagnosis. The bone marrow biopsy showed infiltration by Hodgkin's disease in only three individuals (3.3%); two of these patients displayed constitutional symptoms and had been assigned to stage III before the biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…although BM involvement has been reported to be less common in Hl when compared to non-Hodgkin lymphomas (4), it is still essential to do BM staging in Hl as it has prognostic significance (5). The incidence of BM involvement in Hl in our study is consistent with the literature, which indicates a range between 3-18 % in many studies (4)(5)(6)(7)(8).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…although BM involvement has been reported to be less common in Hl when compared to non-Hodgkin lymphomas (4), it is still essential to do BM staging in Hl as it has prognostic significance (5). The incidence of BM involvement in Hl in our study is consistent with the literature, which indicates a range between 3-18 % in many studies (4)(5)(6)(7)(8).…”
Section: Discussionsupporting
confidence: 82%
“…Studies have shown that the frequency of BM involvement in Hl is low and varies from 4 to 18% (4)(5)(6)(7). Hence some authors have suggested that BM studies can be done in selected high risk cases alone (5,8,9). However, a controversy exists as few other authors suggest that BM should be done in all the adult cases (1,10).…”
mentioning
confidence: 99%
“…Patients without these clinical factors are unlike to have BM infiltration. Some authors raise the question about the opportunity to perform the BMB in the absence of these features (12). The predictive value of the absence of fever in regard to the absence of BM infiltration is 98% (13).…”
Section: Clinical and Laboratory Datamentioning
confidence: 99%
“…In this respect, it has previously been shown that only about 2% of patients in this population with HL have a positive BM biopsy. 13 …”
Section: Methodsmentioning
confidence: 99%